2021
DOI: 10.1016/j.jiph.2021.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of tocilizumab in patients with severe COVID-19: Survival and clinical outcomes

Abstract: Background SARS-CoV-2 is associated with a severe inflammatory response contributing to respiratory and systemic manifestations, morbidity, and mortality in patients with coronavirus disease 2019 (COVID-19). Methods Tocilizumab (TCZ) efficacy on mortality and length of hospital stay was retrospectively evaluated in patients who received TCZ and compared with that in controls with a similar severity of COVID-19. The primary endpoint was survival probability on day 28. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
(36 reference statements)
0
9
1
1
Order By: Relevance
“…Among studies that assessed the mortality of COVID-19 patients on tocilizumab in Saudi Arabia, our study reported an overall mortality of 21%. In comparison, other studies reported 16.1% (n = 62) 28-day mortality [36]. In terms of mortality among ICU patients, the current study reported 38.5%, while other studies reported 31.1% (n = 61) [37] and 18.9% (n = 37) [38] mortality.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Among studies that assessed the mortality of COVID-19 patients on tocilizumab in Saudi Arabia, our study reported an overall mortality of 21%. In comparison, other studies reported 16.1% (n = 62) 28-day mortality [36]. In terms of mortality among ICU patients, the current study reported 38.5%, while other studies reported 31.1% (n = 61) [37] and 18.9% (n = 37) [38] mortality.…”
Section: Discussioncontrasting
confidence: 88%
“…Hypercytokinemia and its associated hyperinflammatory and immunodeficiency are reported to be responsible for lethal complications and increased mortality in COVID-19 patients [ 6 , 33 , 34 , 35 , 36 ]. Accordingly, the findings of this study provide valuable detail to guide the use of tocilizumab in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent research article, a trial that examined survival varied with baseline CRP levels demonstrated the administration of Tocilizumab was beneficial in patients with CRP levels greater than 15.0 g/L [ 21 ]. Some studies have also evaluated the Tocilizumab treatment in patients with severe COVID-19, suggesting its efficacy on mortality [ 22 , 23 , 24 ]. The TCZ efficacy on mortality on day 14 and 28 was retrospectively evaluated in 62 patients (57.4 ± 14.3 years) who received one to two doses of TCZ (400–800 mg every 12 h) [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have also evaluated the Tocilizumab treatment in patients with severe COVID-19, suggesting its efficacy on mortality [ 22 , 23 , 24 ]. The TCZ efficacy on mortality on day 14 and 28 was retrospectively evaluated in 62 patients (57.4 ± 14.3 years) who received one to two doses of TCZ (400–800 mg every 12 h) [ 22 ]. There was a significant difference in the 28-day (TCZ = 62 and control = 86) and in the 14-day (9.7% vs. 24.4%, p = 0.022) fatality rate among the TCZ-treated patients and control group.…”
Section: Discussionmentioning
confidence: 99%
“…In COVID-19 related cytokine storm syndrome (COVID-CSS), different inflammatory cytokines such as Interleukin-1 (IL-1), Interleukin-10 (IL-10), and tumor necrosis factor (TNF)-α are elevated about 2-100 fold above normative values. In some patients with COVID-19, IL-6 levels rise more than 1,000 fold above normal range (Blanco-Melo et al, 2020;Herold et al, 2020;Laing et al, 2020;Al-Baadani et al, 2021). IL-6 signals through both classic and trans-signaling pathways, activates JAK-STAT3 signaling.…”
Section: Does Immune Dysregulation Predisposes Individual To Cancer Il-6/jak/stat Signaling Pathwaymentioning
confidence: 99%